Male circumcision and the enhancement debate: harm reduction, not prohibition - Savulescu, Julian (Journal of medical ethics, 2013)
Around a third of men worldwide are circumcised. It is probably the most commonly performed surgical procedure. Circumcision is also one of the oldest forms of attempted human enhancement. It is and has been done for religious, social, aesthetic and health reasons. Circumcision has a variety of benefits and risks, many of which are discussed in this issue. There is some dispute about the magnitude and likelihood of these benefits and risks. Some argue that the risks outweigh the benefits and circumcision should not be performed on children who are not competent to make their own decisions. If the risks of circumcision clearly outweighed the benefits, great harm has been done and is being done globally through this procedure. Around a third of all men would have been harmed. This is an extraordinary public health injury. Presumably, many would be entitled to compensation. The fact that relatively few people think that the situation is as bad as this indicates that most people implicitly believe that circumcision is not generally a significant harm, if a harm at all. (This is an example of the kind of argument called modus tollens. If p, then q. Not-q, therefore not-p.) One might thus conclude either that: It is not clear from existing evidence whether the risks of properly performed circumcision outweigh the benefits, or vice versa. Or 2. If circumcision is against the interests of an infant or young child, it is only mildly so. In general, people should make their own decisions about body modification and human enhancement when this is possible. Such an approach speaks in favour of waiting until a child becomes an adult to make his or her own decision about circumcision. And procedures which are not clearly in a child's interests should not be performed on that child. However, religious …